Anterior tibial compartment syndrome following femoral artery perfusion. Issue 4 (July 1973) - Palmer, B. V.; Mercer, J. L.
Abstract : Palmer, B. V., and Mercer, J. L. (1973). Thorax, 28, 492-494. Anterior tibial compartment syndrome following femoral artery perfusion. Four patients are described who developed the anterior tibial compartment syndrome following open heart surgery. It occurred in the limb used for femoral artery perfusion in each patient. In two it was known that the collateral circulation to the limb was also considerably impaired. It is suggested that prolonged limb ischaemia is the major initiating factor. The treatment of these patients is discussed and although one patient was successfully treated conservatively, surgical treatment is advisable.